Zero-One Law for Connectivity in Superposition of Random Key Graphs on Random Geometric Graphs - Y. Tang; Q. L. Li (Discrete Dynamics in Nature and Society)
We study connectivity property in the superposition of random key graph on random geometric graph. For this class of random graphs, we establish a new version of a conjectured zero-one law for graph connectivity as the number of nodes becomes unboundedly large. The results reported here strengthen recent work by the Krishnan et al.